Effectiveness of Behavioral Counseling Services Self-Management Techniques to Reduce Social Media Addiction in High School Students - Anjani, Kadek Ratna Dwi; Dantes, Nyoman; Dwiarwati, Kadek Ari (Department of Guidance and Counseling, FIP, Undiksha, 2024)
Teenagers who are addicted to social media need to be accompanied to reduce their use of social media, so that they do not continue to depend on social media. This research aims to analyze the effectiveness of behavioral counseling services on self-management techniques to reduce social media addiction in high school students. This type of research is a quasi-experimental research with a nonequivalent pretest-posttest control group design. The population of this study was 199 high school students. Sampling was carried out using purposive sampling technique. The data collection instrument in this research was a social media addiction questionnaire. Data were analyzed using parametric statistical analysis, namely by using paired sample t-test and followed by effect size test. The results of this study show that behavioral counseling services, self-management techniques, are effective in reducing social media addiction in high school students (t = 27.86 with p < 0.05), the results of the hypothesis test posttest score for the experimental class and control class (t = -5.976 with p<0.05), the effect size test results for the experimental class were 10.3, the effect size test results for the control class were 5.61, and the effect size test results for the posttest scores for the experimental class and control class were -5.45. It can be concluded that there is significant effectiveness of self-management technique behavioral counseling services in reducing social media addiction. The novelty of providing treatment to students with self-management techniques can have implications for changing the paradigm of guidance and counseling teachers in schools when counseling high levels of social media addiction among students.